PERBANDINGAN KETAHANAN DAUN CABAI RAWIT DAN TOMAT TERHADAP SERANGAN Thrips sp. BERBASIS PENGOLAHAN CITRA DIGITAL - QAEFA YUHAJIRIN; RAHAYU MALLARANGENG; ASMAR HASAN; ANDI KHAERUNI; TERRY PAKKI; ABDUL RAHMAN (Jurnal Agroteknos, 2023)
The presence of thrips pests that attack the leaves of cayenne pepper and tomato can cause high yield losses in both crops. Plant resistance to thrips is thought to be related to the pest's preference for plant leaves. The difference in the resistance level of the two plants to thrips attack needs to be studied based on a digital image processing approach as an accurate method of assessing plant damage. This study compares the resistance of cayenne pepper and tomato leaves to thrips attack based on digital image processing. The study was designed for feed testing with the option of using cayenne pepper and tomato leaves as treatments that were placed in pairs in a testing container. There were five pairs of tests for the first and second repetitions, respectively, and each pair of tests used five individual thrips. The results showed tomato leaves were relatively more resistant to thrips attack because they tended to be less preferred than cayenne pepper. The average area of thrips attack on cayenne pepper leaves for two repetitions of testing was higher than tomato. The assessment of the extent of thrips attack tomato and cayenne pepper leaves based on image processing has high validity, characterized by the accuracy and precision of the assessment results, which reach 80-100%. However, the reliability of the assessment results for two repetitions of testing is still relatively low, especially in assessing damage to cayenne pepper leaves.